Geometry of algebraic curves. - Arbarello, E.; Cornalba, M. (Maurizio); Griffiths, Phillip 1938- (Grundlehren der mathematischen Wissenschaften, 2011)
The second volume of the Geometry of Algebraic Curves is devoted to the foundations of the theory of moduli of algebraic curves. Its authors are research mathematicians who have actively participated in the development of the Geometry of Algebraic Curves. The subject is an extremely fertile and active one, both within the mathematical community and at the interface with the theoretical physics community. The approach is unique in its blending of algebro-geometric, complex analytic and topological/combinatorial methods. It treats important topics such as Teichmüller theory, the cellular decomposition of moduli and its consequences and the Witten conjecture. The careful and comprehensive presentation of the material will be of value to students who wish to learn the subject and to experts as a reference source. The first volume appeared 1985 as volume 267 of the same series